Pseudo-differential operators and equations in a discrete half-space - Vasilyev, Alexander V.; Vasilyev, Vladimir B. (Mathematical Modelling and Analysis, 2018)
We introduce a digital pseudo-differential operator acting in discrete Sobolev--Slobodetskii spaces and consider pseudo-differential equations with such operators in a discrete half-space.The theorem on a general solution of such equations is proved for a special case.